Granular active carbon material loaded with ferromanganese bimetallic oxide, preparation method and application of granular active carbon material

By preparing manganese-iron bimetallic oxide granular activated carbon materials using the equal-volume impregnation method and the room-temperature sol-gel method, the problems of cumbersome preparation methods, pore blockage, and metal ion dissolution in existing technologies are solved, achieving efficient and stable water treatment results.

CN121016782APending Publication Date: 2025-11-28SHANDONG SIHAI WATER TREATMENT EQUIP CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511576751.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing methods for preparing iron-manganese bimetallic oxide/activated carbon composite materials suffer from problems such as cumbersome processes, high energy consumption, unsafe solvent use, pore blockage of activated carbon, difficulty in recovering powdered materials, and secondary pollution caused by metal ion leaching.

Method used

Manganese-iron bimetallic oxide granular activated carbon material was prepared by using an equal-volume impregnation method combined with room-temperature sol-gel method and high-temperature calcination technology. The manganese-iron-citric acid sol was uniformly dispersed in the activated carbon pores to avoid high-temperature agglomeration and pore blockage. Acetates and nitrates were used to replace chlorides to ensure the stability of metal ions.

Benefits of technology

It enables large-scale production of materials, generates no waste liquid, prevents clogging of activated carbon pores, and minimizes metal ion leaching, providing a water treatment solution with high catalytic performance and long lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016782A_ABST
    Figure CN121016782A_ABST
Patent Text Reader

Abstract

The invention relates to a ferromanganese bimetallic oxide-loaded granular active carbon material, a preparation method and application thereof, and belongs to the technical field of environmental functional materials and water treatment.The preparation method comprises the following steps: determining the saturated water absorption volume of granular active carbon per unit mass; the preparation method comprises the following steps: sequentially and completely dissolving manganese acetate tetrahydrate and iron nitrate nonahydrate in deionized water, then adding citric acid monohydrate, and fully stirring for reaction to obtain a manganese-iron-citric acid sol system; putting the dried granular activated carbon into a manganese-iron-citric acid sol system, uniformly stirring, and standing to obtain iron-manganese impregnated granular activated carbon; transferring the iron-manganese impregnated granular activated carbon into a drying oven for drying to obtain dried iron-manganese impregnated granular activated carbon; the dry iron-manganese impregnated granular active carbon is calcined under the oxygen-limited or oxygen-free condition, equivalent-volume impregnation, a normal-temperature sol-gel method and a high-temperature calcination technology are combined, no organic solvent or high-pressure equipment is needed, operation is safe, no waste liquid is generated, and large-scale production of materials is easy to achieve.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of environmental functional materials and water treatment technology, and particularly relates to a manganese-iron bimetallic oxide loaded granular activated carbon material, a preparation method and application thereof. BACKGROUND

[0002] The refractory organic wastewater is characterized by large discharge amount, high organic load, highly complex composition and difficulty in biodegradation, and has become a key bottleneck restricting the improvement of water treatment process efficiency and the upgrading of standards. In the research of seeking solutions, the advanced oxidation pathway based on peroxymonosulfate (PMS) has been highly valued in recent years.

[0003] This technical system is significantly different from the traditional Fenton method: first, its dependence on solution acidity is greatly reduced, and the applicable pH range is significantly widened; second, it does not need to use hydrogen peroxide which has high risk of storage and transportation. The main product of activated PMS is sulfate radical (SO4·−), which has higher oxidation ability than common hydroxyl radicals, and can effectively remove stubborn organic pollutants.

[0004] In addition, PMS advanced oxidation technology can also use singlet oxygen generation, direct electron transfer mechanism and high-valent metal oxidation mechanism to realize the structural damage of pollutants.

[0005] Using transition metal oxides to catalyze and activate PMS to generate highly active oxygen species is the core strategy to greatly improve the degradation rate. Among the many available catalysts, iron and manganese-based oxide materials are considered as the preferred choice for PMS oxidation system due to their easy availability, excellent economy, low environmental hazard and good activation efficiency. However, single-component iron oxide catalysts have the shortcoming of easy deactivation or low efficiency under certain conditions; while manganese oxides face the dilemma of their own dissolution, which not only causes the loss of active components, but also may cause the risk of secondary pollution of metal ions.

[0006] To synergistically optimize performance and stability, composite iron-manganese bimetallic oxides exhibit advantages through the interaction between components: improving the structural stability of the catalyst, inhibiting the dissolution loss of active components and improving the activation efficiency. However, nanoscale iron-manganese bimetallic particles face serious agglomeration tendency when applied in actual water treatment scenarios, which results in a sharp decrease in effective reaction contact area and deterioration of dispersion state; at the same time, the separation and recovery process is complex and the material loss is serious.

[0007] An effective way to overcome these application barriers is to construct supported catalysts, i.e., immobilize the iron-manganese bimetallic oxide component on a support with a developed pore structure. This supported design can effectively inhibit the coalescence of nanoparticles through physical isolation, significantly improve the utilization rate of active sites, and greatly facilitate subsequent recovery and reuse operations, thereby laying the foundation for the final landing of this technology in real wastewater treatment projects.

[0008] Activated carbon has a highly developed pore structure, containing abundant micropores, mesopores, and part of macropores, forming a large specific surface area and complex pore network, which provides sufficient loading sites and spatial confinement for nano iron-manganese bimetallic oxides. It has high mechanical strength, stable chemical properties, and good hydrophilicity, can effectively load and immobilize active components, maintain their high dispersion state, and expose more active sites. The preparation methods of iron-manganese bimetallic oxide / activated carbon composite materials are listed as follows: Patent CN119500176A dissolves anhydrous ferric nitrate and anhydrous manganese nitrate in anhydrous ethanol to form a metal alkoxide solution, then adds an activated carbon carrier (particle size 4-6 mm, mass to ethanol volume ratio 1:10), separates after stirring in a 60°C water bath for 2 hours, dries at 105°C for 12 hours and calcines at 600°C for 8 hours to obtain a supported manganese-iron oxide ozone catalyst. This process relies on highly volatile anhydrous ethanol as a solvent, undoubtedly increasing the production safety hazards and operational complexity, limiting the flexibility of industrial applications.

[0009] Patent CN119346129A adds activated carbon fiber powder to an iron-manganese metal salt solution, adjusts the pH to 7-10, ages, filters, washes, dries, and calcines to obtain a precursor; then mixes the precursor with aluminum gel, acidifies and bonds, and finally dries and calcines to form. This method has significant defects: the process is complicated, involves two high-temperature treatments, has high energy consumption and is prone to sintering of active components; the aluminum gel and acidification steps increase raw material costs and operational complexity, affecting industrial-scale applications.

[0010] Most existing technologies use solvothermal method, chemical co-precipitation method, hydrothermal method or a combination of multiple methods (such as hydrothermal-ultrasonic composite process, chemical co-precipitation-hydrothermal method, water bath-reverse co-precipitation method, etc.), which generally have the problems of complicated process and multiple steps; and involve high temperature (80-180°C), high pressure reaction conditions, some require nitrogen protection, and often use time-consuming and energy-consuming post-processing methods such as vacuum drying and freeze-drying, which not only have low energy efficiency, but also have potential operational safety risks.

[0011] Some methods rely on toxic or highly volatile solvents such as ethylene glycol, which are difficult to recover and can cause environmental pollution and increase processing costs; some methods require the addition of auxiliary reagents such as polyethylene glycol and sodium acetate, or the use of specific reagents such as ammonia and potassium permanganate, which increase raw material costs and operational complexity.

[0012] Most preparation methods can easily lead to uneven dispersion of iron-manganese bimetallic oxides (or manganese ferrite) on the surface of activated carbon, local agglomeration, and even sintering of active components; at the same time, it generally causes a large decrease in the specific surface area of activated carbon (the loss rate is as high as 70% in some methods), and serious pore blockage, which leads to insufficient exposure of active sites and limited active reaction space; some methods use a “secondary compounding” rather than “in-situ synthesis” loading method, which further reduces the loading stability.

[0013] The carrier is mostly powdered activated carbon (mesh number is mostly 100-300 mesh), which does not fundamentally avoid the problems of easy loss and difficult recovery of powdered materials.

[0014] Based on the above analysis, the preparation of the existing iron-manganese bimetallic oxide / activated carbon composite material still has the following deficiencies: (1) it is severely dependent on a liquid phase reaction system, mostly involving co-precipitation and hydrothermal reaction processes, the process is relatively complicated, the requirements for the preparation conditions are harsh, and a large amount of waste liquid is generated; (2) the existing synthesis methods generally cause pore blockage of activated carbon, serious loss of specific surface area, and limited active reaction space when the material is applied; (3) the existing preparation methods usually use powdered activated carbon as the carrier, which still does not fundamentally avoid the problems of loss and difficult recovery of powdered materials; (4) during the catalytic degradation of organic matter by PMS, iron and manganese metal ions usually appear to be dissolved, and the important technical problem of how to reduce the reactivity of metal ions by optimizing the preparation process has not been solved. SUMMARY

[0015] In order to overcome some of the problems mentioned in the above background, the present application provides a manganese-iron bimetallic oxide-loaded granular activated carbon material, a preparation method and applications thereof. The process flow of the present application is simple, no waste liquid is generated, and the manganese-iron bimetallic oxide particles are uniformly dispersed after loading and do not block the original pores of activated carbon. The catalytic material can be directly filled in a fixed bed reactor to catalyze the production of strong oxidizing active species by persulfate to degrade organic pollutants in water, and has extremely low metal ion dissolution, does not produce secondary pollution, and can provide a new type of catalytic material with great application potential for actual advanced oxidation water treatment engineering, to at least partially solve the above problems.

[0016] According to the technical scheme of the present application, a manganese-iron bimetallic oxide-loaded granular activated carbon material is provided, comprising the following steps: S1. determining the saturated water absorption volume of unit mass of granular activated carbon; S2. completely dissolving manganese acetate tetrahydrate and iron nitrate nonahydrate in deionized water in sequence, then adding citric acid monohydrate, and obtaining a manganese-iron-citric acid sol system after fully stirring and reacting; S3. Put the dry granular activated carbon into the manganese-iron-citric acid sol system, stir uniformly, and then stand to obtain the iron-manganese impregnated granular activated carbon; S4. Transfer the iron-manganese impregnated granular activated carbon to an oven for drying to obtain dry iron-manganese impregnated granular activated carbon; S5. Perform calcination treatment on the dry iron-manganese impregnated granular activated carbon under oxygen-limited or oxygen-free conditions to obtain a granular activated carbon material loaded with iron-manganese bimetallic oxides.

[0017] Preferably, the raw material of the granular activated carbon includes one or more of coal-based activated carbon and nutshell activated carbon and secondary formed columnar carbon derived from the above raw materials; the particle size of the granular activated carbon ranges from 0.2 mm to 5 mm.

[0018] Preferably, the method for determining the saturated water absorption volume of the granular activated carbon includes: completely immerse the completely dried granular activated carbon in deionized water, perform solid-liquid separation by using a filter screen made of a non-water-absorbing material after standing for 24 hours of impregnation, weigh the mass of the water-absorbed saturated activated carbon after no liquid drops, and determine the saturated water absorption volume of the unit mass of activated carbon according to the following formula: , wherein V 饱和 is the saturated water absorption volume of the unit mass of activated carbon, ml / g; m 湿 is the mass of the water-absorbed saturated activated carbon, g; m 干 is the mass of the completely dried granular activated carbon, g; and p is the density of water, 1 g / cm 3 .

[0019] Preferably, the molar ratio of the manganese acetate tetrahydrate and the iron nitrate nonahydrate is 1:(2-3.5); and the molar ratio of the citric acid monohydrate to the total amount of the manganese acetate tetrahydrate and the iron nitrate nonahydrate is (1.2-1.5):1. The manganese-iron-citric acid sol system is obtained by stirring for 30-120 minutes at room temperature.

[0020] Preferably, a rare earth metal salt is added during the process of completely dissolving the manganese acetate tetrahydrate and the iron nitrate nonahydrate in deionized water in sequence, and the molar ratio of the rare earth metal salt to the total amount of the manganese acetate tetrahydrate and the iron nitrate nonahydrate is (0.05-0.1):1, and the rare earth metal salt includes cerium nitrate hexahydrate and / or lanthanum nitrate hexahydrate.

[0021] Preferably, the added amount of the dry granular activated carbon in step S3 is calculated according to the following formula: m=V 水 / V 饱和 , wherein m is the added mass of the dry activated carbon, g; V水 V is the volume of deionized water in step S2, ml; V 饱和 V is the saturated water absorption volume of unit mass of activated carbon, ml / g; the standing time in step S3 is 6-24 h.

[0022] Preferably, the temperature of drying in the oven in step S4 is 80-120℃, and the drying time is 6-24 h. During the drying in the oven, the material is stirred every 5 min within 30 min after the start of drying.

[0023] Preferably, the calcination treatment in step S5 comprises the following steps: The dried iron-manganese impregnated granular activated carbon is placed in a crucible, covered and wrapped with double-layer aluminum foil, and then placed in a muffle furnace for calcination, wherein the heating rate of the muffle furnace is 1-10℃ / min, the highest calcination temperature is 400-700℃, and the holding time is 1-6 h; or the dried iron-manganese impregnated granular activated carbon is placed in a crucible and then transferred to an atmosphere tube furnace for calcination under the protection of an inert gas, wherein the heating rate in the atmosphere tube furnace is 1-10℃ / min, the highest calcination temperature is 400-700℃, and the holding time is 1-6 h, and the inert gas includes high-purity nitrogen and / or argon, and the gas flow rate is 50-300 mL / min.

[0024] Preferably, the calcined granular activated carbon loaded with manganese-iron bimetallic oxide is soaked in a 0.1-0.5 mol / L tetrabutyl titanate-ethanol solution, and stirred at room temperature for 1-2 hours; transferred to an oven for drying at 80-120℃ for 6-24 h, and then calcined at 400-500℃ in an air atmosphere for 1-2 h to generate anatase TiO2 in situ on the surface of the activated carbon.

[0025] Further, the present application also provides a granular activated carbon material loaded with manganese-iron bimetallic oxide, which is prepared according to the above-mentioned preparation method of the granular activated carbon material loaded with manganese-iron bimetallic oxide.

[0026] On the other hand, the present application also provides an application of a granular activated carbon material loaded with manganese-iron bimetallic oxide, which is prepared according to the above-mentioned preparation method of the granular activated carbon material loaded with manganese-iron bimetallic oxide and applied in the field of environmental functional materials and water treatment technology.

[0027] Compared with the prior art, the present application has the following beneficial effects: The present application avoids hydrothermal and co-precipitation processes with high control precision requirements by combining equal-volume impregnation, normal-temperature sol-gel method and high-temperature calcination technology, and does not need organic solvents or high-pressure equipment, so that the operation is safe and no waste liquid is generated, and the scale production of the material is easy to realize; In the present application, the manganese-iron-citric acid sol is precisely filled in the pore channels of the activated carbon by the equal-volume impregnation method, instead of being accumulated on the surface; during the drying process, the sol is dehydrated and polycondensed into xerogel, and the metal ions are fixed in the citric acid molecular network and cannot migrate and aggregate; in addition, the physical isolation of the pore wall enables the manganese-iron-citric acid xerogel to grow in situ in the nanoscale space, and the above-mentioned effects realize the uniform dispersion of the bimetallic oxide precursor; In the present application, the carbon layer generated by pyrolysis of citric acid temporarily coats the nascent bimetallic oxide microcrystals, blocks the direct contact between the microcrystals, and avoids the surface diffusion of metal atoms and the grain coalescence and growth at high temperatures; in addition, the size of the bimetallic oxide particles is physically constrained by the activated carbon pores during the high-temperature growth process, and finally the in-situ anchoring of the uniform-nanoparticle-sized particles is realized, which ensures that the activated carbon pores are not blocked and sufficient reaction space is reserved, and more active sites are exposed; In the present application, the particle activated carbon with a particle size of 0.2-5 mm is selected as the carrier, which can be directly filled into a fixed bed reactor to avoid the problem of loss of powder materials; manganese acetate and ferric nitrate are used instead of commonly used chloride salts, and high-temperature decomposition is complete without harmful residues; the spinel structure firmly locks the metal ions, and the dissolution of iron and manganese ions during the catalytic process is extremely small, which avoids secondary pollution and provides a solution with high activity, long service life and controllable cost for advanced oxidation water treatment projects. BRIEF DESCRIPTION OF DRAWINGS

[0028] Figure 1 It is a scanning electron microscope image of the material prepared in Example 1 of the present application; Figure 2 It is an X-ray diffraction spectrum of the material prepared in Example 1 of the present application; Figure 3 It is an N2 adsorption-desorption curve and pore parameter of the material prepared in Example 1 of the present application; Figure 4 It is an electron paramagnetic resonance spectrum of the material prepared in Example 1 of the present application; Figure 5 It is the rhodamine B removal rate corresponding to different experimental schemes in Application Example 1 of the present application; Figure 6 It is a schematic diagram of a continuous flow fixed bed catalytic experimental device used in Application Example 2 of the present application; Figure 7 It is a variation curve of the removal rate of lomefloxacin in the continuous flow catalytic experiment in Application Example 2 of the present application. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application; based on the embodiments, all other embodiments obtained by a person of ordinary skill in the art without creative effort fall within the protection scope.

[0030] The embodiment of the present application provides a granular activated carbon loaded with iron-manganese bimetallic oxide and a preparation method thereof, which comprises the following steps: (1) a certain mass (m 干 ) of completely dried granular activated carbon is completely immersed in deionized water, and after standing for 24 hours, solid-liquid separation is performed by using a filter screen made of a non-water-absorbing material; after no liquid drops, the mass (m 湿 ) of the water-absorbed saturated activated carbon is weighed. The saturated water-absorbed volume (V) of the unit mass of activated carbon is determined according to the following formula: , wherein, ρ is the density of water (1 g / cm 3 ).

[0031] (2) manganese acetate tetrahydrate, iron nitrate nonahydrate and rare earth metal salt or manganese acetate tetrahydrate and iron nitrate nonahydrate are completely dissolved in deionized water with a volume of V 水 in a certain molar ratio, and a certain mass of citric acid monohydrate is added to the manganese-iron mixed solution, and the solution is fully stirred at room temperature to obtain a manganese-iron-citric acid sol system; (3) the dried granular activated carbon with a mass of m (m=V 水 / V 饱和 ) is placed in the manganese-iron-citric acid sol system, and after being rapidly stirred and uniformly mixed, the solution is left to stand for a period of time to obtain iron-manganese impregnated granular activated carbon; (4) the iron-manganese impregnated granular activated carbon is transferred to an oven for complete drying to obtain dried iron-manganese impregnated granular activated carbon; (5) the dried iron-manganese impregnated granular activated carbon is subjected to calcination treatment under oxygen-limited or oxygen-free conditions to obtain a granular activated carbon material loaded with iron-manganese bimetallic oxide, and then the calcined granular activated carbon loaded with manganese-iron bimetallic oxide is soaked in a 0.1-0.5 mol / L tetrabutyl titanate-ethanol solution, and stirred at room temperature for 1-2 hours; transferred to an oven for drying at 80-100°C for 6-24 hours, and then calcined in an air atmosphere at 400-500°C for 1-2 hours to generate anatase TiO2 in situ on the surface of the activated carbon.

[0032] To avoid the generation of residual waste liquid, the equal volume impregnation method is adopted. Therefore, the saturated water absorption volume of unit mass of granular activated carbon should be determined first, and then the impregnation liquid of appropriate volume is prepared according to the subsequent preparation of the amount of activated carbon raw material to ensure that the impregnation liquid is completely absorbed by the activated carbon.

[0033] The type of anion constituting the metal salt directly affects the stability of the metal oxide. Acetate is more easily decomposed completely during heating, first dehydrating and forming basic acetate, and then decomposing into carbon dioxide (CO2), water (H2O) and metal oxide above 300-400℃. These decomposition products are gases and inorganic oxides, and there are basically no harmful residues in the products, which will not promote the dissolution of the metal.

[0034] Nitrates mainly decompose into gaseous products (NO x , O2, H2O) and metal oxides during heating. The decomposition is usually complete, and it is not easy to leave harmful ions, and finally clean oxides are obtained. In contrast, chloride ions may be wrapped around metal particles during high-temperature processes, delaying their complete decomposition, resulting in poor crystallinity, large particles and instability of the formed metal species, and relatively high solubility in acidic or neutral water.

[0035] In a further embodiment of the present embodiment, the manganese salt and the iron salt adopted by the present scheme are manganese acetate tetrahydrate and ferric nitrate nonahydrate, respectively, and a mixed solution of manganese acetate and ferric nitrate is prepared, and the addition ratio of the two is particularly critical. When the molar ratio of manganese atoms to iron atoms is 1:2, it is beneficial to form a highly crystalline spinel phase of MnFe2O4, which has a stable structure and metal ions are firmly locked in the lattice. A slight excess of Fe(III) can compensate for oxygen vacancies or promote the increase of manganese valence, making the manganese in the lattice more stable.

[0036] However, if the addition amount of ferric nitrate is significantly too high, it may lead to the formation of α-Fe2O3 heterogeneous phase, which has almost no PMS catalytic activity under neutral pH conditions. In addition, if the addition amount of manganese acetate is too high, manganese oxides such as Mn2O3 and MnO may be formed, which have poorer PMS activation performance and structural stability during the catalytic process than MnFe2O4.

[0037] In a further embodiment of the present embodiment, the molar ratio of the manganese acetate tetrahydrate and the ferric nitrate nonahydrate is 1:3.5-1:2; after the manganese acetate tetrahydrate and the ferric nitrate nonahydrate are completely dissolved, a certain mass of citric acid monohydrate is added to the deionized water, and stirred at room temperature for a period of time. Before adding the citric acid monohydrate, a small amount of rare earth metal salt, cerium nitrate hexahydrate and / or lanthanum nitrate hexahydrate, can also be added. The outer electrons of the rare earth elements can form coordination bonds with Mn 2+ / Mn 3+ / Mn 4+ , Fe 2+ / Fe3+ Forming "electron transfer bridge", reducing PMS activation energy barrier, improving OH, SO 4・ - The active oxygen generation rate is equal, and the rare earth oxide can fill the oxygen vacancies of the MnFe2O4 spinel structure and inhibit the dissolution of metal ions.

[0038] Citric acid acts as a metal ion complexing agent in this process, promoting the formation of a sol-gel system. Citric acid (a multidentate ligand) forms stable water-soluble complexes with metal ions (Mn 2+ , Fe 3+ ) through carboxyl groups (-COOH) and hydroxyl groups (-OH). This process enables the uniform mixing of metal ions at the molecular level in the solution. In addition, the metal ions are wrapped by citric acid molecules, and the electrostatic repulsion is enhanced, effectively preventing premature agglomeration due to hydrolysis or electrostatic attraction during the impregnation stage. An excess of citric acid is usually required to ensure sufficient complexation and sol formation. Too little citric acid can result in uneven complexation of metal ions; too much citric acid can result in excessive carbon residue after pyrolysis, which can coat the active sites.

[0039] In a further embodiment of the present embodiment, the molar ratio of the citric acid dosage to the total dosage of manganese and iron metal salts is 1.2:1-1.5:1; the sol-gel reaction time is 30-120 minutes; and a certain amount of granular activated carbon is added to the manganese-iron-citric acid sol-gel system. To ensure that the sol-gel impregnation solution is completely absorbed by the granular activated carbon, the amount of activated carbon added should be calculated strictly according to the volume of deionized water added when preparing the sol-gel system and the water absorption rate of the granular activated carbon.

[0040] After adding the granular activated carbon to the manganese-iron-citric acid sol-gel system, it should be stirred quickly and uniformly to ensure that the solid particles are in full contact with the impregnation solution, and then left to stand for a period of time to allow the activated carbon to be completely infiltrated.

[0041] In a further embodiment of the present embodiment, the standing time is 6-24 hours; and the iron-manganese-impregnated granular activated carbon is transferred to an oven for drying. The purpose of this step is to evaporate and condense the sol inside the activated carbon pores to form a xerogel. In this process, manganese and iron ions are anchored in the citric acid molecular network, obtaining a precursor with atomic-scale uniformity. After calcination, a precise oxide solid solution without phase segregation is directly generated, which is crucial for the preparation of multi-metal oxides.

[0042] In a further embodiment of the present embodiment, the drying temperature is 80-120°C; the drying time is 6-24 hours; and the material should be turned over every 5 minutes within 30 minutes after the start of drying to ensure uniform heating.

[0043] In a further implementation form of the embodiment, the dried iron-manganese impregnated granular activated carbon is subjected to high-temperature calcination treatment to convert the manganese-iron-citric acid xerogel inside the pores of the activated carbon into manganese-iron bimetallic oxide. To avoid high-temperature combustion and ashing of the activated carbon carrier, the calcination process should be carried out under limited oxygen or no oxygen conditions; to ensure complete pyrolysis of citric acid and avoid the formation of elemental metal caused by high-temperature carbon thermal reduction, the calcination temperature and time should be reasonably set.

[0044] In a further implementation form of the embodiment, the calcination equipment is a muffle furnace or an atmosphere tube furnace; the calcination method is to place the precursor in a crucible, cover it and wrap it with at least two layers of aluminum foil, and then place it in the muffle furnace for calcination; or place the precursor in a crucible and then place it in the atmosphere tube furnace for calcination under the protection of inert gas.

[0045] In a further implementation form of the embodiment, the inert gas is high-purity nitrogen, high-purity argon, or any ratio of mixed gas thereof; the calcination temperature is 400-700℃; the heating rate is 1-10℃ / min; the calcination time is 1-6h; and the gas flow rate is 50-300mL / min.

[0046] TiO2 generates photo-generated electrons (e - ) and holes (h + ) under light, e - can reduce Fe 3+ → Fe 2+ and Mn 4+ → Mn 3+ , promote metal valence cycle, and thus accelerate PMS activation; h + can directly oxidize organic matter, supplement active oxygen species, and the TiO2 loading adopts “low-temperature calcination (400-500℃)”, which will not damage the formed MnFe2O4 spinel structure.

[0047] Further, the embodiment of the present application also provides a granular activated carbon material loaded with manganese-iron bimetallic oxide, which is prepared according to the preparation method of the granular activated carbon material loaded with manganese-iron bimetallic oxide.

[0048] On the other hand, the embodiment of the present application also provides an application of the granular activated carbon material loaded with manganese-iron bimetallic oxide, which is prepared according to the preparation method of the granular activated carbon material loaded with manganese-iron bimetallic oxide and applied in the field of environmental functional materials and water treatment technology.

[0049] Embodiment 1: The preparation process of the granular activated carbon loaded with iron-manganese bimetallic oxide is as follows: (1) Place 1g of coconut shell granular activated carbon with a particle size of 2-4mm in 10mL of deionized water and let it stand for 24 hours. Then, use a stainless steel filter screen to separate the solid and liquid. After no more liquid drips, weigh the water-absorbing activated carbon and find that the mass is 1.50g. The saturated water absorption volume of the coconut shell granular activated carbon per unit mass is 0.5mL.

[0050] (2) 1.8382 g (0.0075 mol) of manganese acetate tetrahydrate and 6.06 g (0.015 mol) of ferric nitrate nonahydrate were added to 10 mL of deionized water and stirred until completely dissolved. 5.6738 g (0.027 mol) of citric acid monohydrate was added to the manganese-iron mixed solution and stirred at room temperature for 60 minutes to obtain the manganese-iron-citric acid sol system.

[0051] (3) Add 20 grams of coconut shell granular activated carbon to the manganese-iron-citric acid sol system, stir quickly and evenly, and let stand for 12 hours.

[0052] (4) Transfer the manganese-iron impregnated coconut shell granular activated carbon to an oven and dry at 105°C for 6 hours.

[0053] (5) The dried manganese-iron impregnated coconut shell granular activated carbon was transferred to an atmosphere tube furnace, and heated to 650°C at a rate of 5°C / min under nitrogen purging at 300 mL / min. The temperature was held for 2 hours, and then naturally cooled to room temperature under nitrogen protection to obtain granular activated carbon loaded with manganese-iron bimetallic oxide.

[0054] Scanning electron microscope (SEM) images of the granular activated carbon loaded with iron-manganese bimetallic oxides prepared in Example 1 are shown below. Figure 1 As shown, it exhibits a rough, porous structure with a large number of uniformly sized nanoparticles uniformly loaded on the pore wall surface. Figure 2 The X-ray diffraction (XRD) pattern of the material prepared in Example 1 shows that, in addition to the broad peaks of amorphous carbon belonging to activated carbon, a series of diffraction peaks belonging to manganese ferrite (MnFe2O4) can also be observed, proving the successful loading of the bimetallic oxide. Figure 3 The N2 adsorption-desorption curves and pore parameters of the composite material prepared in Example 1 and the original coconut shell activated carbon are shown. The specific surface areas of the original carbon and the composite material are 1019 and 962 m², respectively. 2 / g, the attenuation rate after loading is only 5.6%, indicating that the preparation method used in Example 1 can retain the original pore structure of the activated carbon carrier to a great extent. Figure 4 This is the electron paramagnetic resonance (EPR) spectrum of the material prepared in Example 1, showing that significant hydroxyl radicals (×OH) and sulfate radicals (SO₄²⁻) can be observed after mixing the material with PMS for 1 minute. 4× - ), superoxide radicals (O 2× -) and singlet oxygen ( 1 The signal peak of O2 indicates that the catalytic reaction involves both free radical and non-free radical pathways.

[0055] Example 2: The preparation process of granular activated carbon loaded with iron-manganese bimetallic oxides is as follows: (1) Place 1g of coal-based briquetted granular activated carbon with a particle size of 1-3mm into 10mL of deionized water. After standing for 24 hours, use a nylon filter screen for solid-liquid separation. After no more liquid drips, weigh the water-absorbing activated carbon and find that the mass is 1.60g. The saturated water absorption volume of the coconut shell granular activated carbon per unit mass is 0.6mL.

[0056] (2) 1.1029 g (0.0045 mol) of manganese acetate tetrahydrate and 6.06 g (0.015 mol) of ferric nitrate nonahydrate were added to 10 mL of deionized water and stirred until completely dissolved. 6.1466 g (0.0293 mol) of citric acid monohydrate was added to the manganese-iron mixed solution and stirred at room temperature for 120 minutes to obtain the manganese-iron-citric acid sol system.

[0057] (3) Add 16.67 grams of coal-based briquetted crushed granular activated carbon to the manganese-iron-citric acid sol system, stir quickly and evenly, and let stand for 24 hours.

[0058] (4) Transfer the manganese-iron impregnated coal-based briquetted granular activated carbon to an oven and dry it at 80°C for 12 hours.

[0059] (5) Transfer the dried manganese-iron impregnated coal-based briquetted granular activated carbon to a corundum boat, cover it and wrap it with two layers of aluminum foil, put it in a muffle furnace, heat it to 550°C at a rate of 2°C / min, keep it at that temperature for 3 hours, and then cool it naturally to room temperature to obtain granular activated carbon loaded with manganese-iron bimetallic oxide.

[0060] Example 3: The preparation process of granular activated carbon loaded with iron-manganese bimetallic oxides is as follows: (1) Place 1g of apricot shell granular activated carbon with a particle size of 2-4mm in 10mL of deionized water, let it stand for 24 hours, and then use a nylon filter screen to separate the solid and liquid. After no more liquid drips, weigh the water-absorbing activated carbon and find that the mass is 1.43g. The saturated water absorption volume of a unit mass of coconut shell granular activated carbon is 0.43mL.

[0061] (2) 1.47 g (0.006 mol) of manganese acetate tetrahydrate and 6.06 g (0.015 mol) of ferric nitrate nonahydrate were added to 10 mL of deionized water and stirred until completely dissolved. 5.7368 g (0.0273 mol) of citric acid monohydrate were added to the manganese-iron mixed solution and stirred at room temperature for 30 minutes to obtain the manganese-iron-citric acid sol system.

[0062] (3) Add 23.26 g apricot shell granular activated carbon into the manganese-iron-citric acid sol system, stir rapidly and uniformly, and then stand for 10 hours.

[0063] (4) Transfer the manganese-iron impregnated apricot shell granular activated carbon into an oven, dry at 100°C for 8 hours.

[0064] (5) Transfer the dried manganese-iron impregnated coal briquette broken granular activated carbon into a corundum boat, cover and wrap with two layers of aluminum foil, place into a muffle furnace, heat to 600°C at a rate of 2°C / min, keep for 2 h, naturally cool to room temperature, and then obtain the granular activated carbon loaded with manganese-iron bimetallic oxides.

[0065] Comparative Example 1: The preparation process of the carbon ball loaded with manganese-iron bimetallic oxides is as follows: (1) Add 1.8382 g of manganese acetate tetrahydrate, i.e. 0.0075 mol, and 6.06 g of iron nitrate nonahydrate, i.e. 0.015 mol, into 10 mL of deionized water in sequence, and stir until completely dissolved; add 5.6738 g of citric acid monohydrate, i.e. 0.027 mol, into the manganese-iron mixed solution, and stir at room temperature for 60 minutes to obtain a manganese-iron-citric acid sol system.

[0066] (2) Transfer the beaker containing the manganese-iron-citric acid sol system into an oven, and dry at 105°C until completely dehydrated.

[0067] (5) Transfer the dried manganese-iron-citric acid xerogel into a tube furnace in an atmosphere, heat to 650°C at a rate of 5°C / min under the blowing of nitrogen at a rate of 300 mL / min, keep for 2 h, and then naturally cool to room temperature under the protection of nitrogen to obtain manganese-iron bimetallic oxides.

[0068] Comparative Example 2: The preparation process of the granular activated carbon loaded with manganese-iron bimetallic oxides is as follows: (1) Put 1 g of coconut shell granular activated carbon with a particle size of 2-4 mm into 10 mL of deionized water, stand for 24 hours, and then perform solid-liquid separation with a stainless steel filter screen. After no liquid drops, weigh the mass of the water-absorbed activated carbon as 1.50 g, and the saturated water absorption volume of the unit mass of the coconut shell granular activated carbon is 0.5 mL.

[0069] (2) Add 1.4843 g of manganese chloride tetrahydrate, i.e. 0.0075 mol, and 4.0545 g of iron chloride hexahydrate, i.e. 0.015 mol, into 10 mL of deionized water in sequence, and stir until completely dissolved; add 5.6738 g of citric acid monohydrate, i.e. 0.027 mol, into the manganese-iron mixed solution, and stir at room temperature for 60 minutes to obtain a manganese-iron-citric acid sol system.

[0070] (3) 20 g of coconut shell granular activated carbon was added into the manganese-iron-citric acid sol system, and stirred rapidly to be uniform, and then was left to stand for 12 hours.

[0071] (4) The manganese-iron impregnated coconut shell granular activated carbon was transferred into an oven, and was dried at 105°C for 6 hours.

[0072] (5) The dried manganese-iron impregnated coconut shell granular activated carbon was transferred into a tube furnace, and was heated to 650°C at a rate of 5°C / min under the blowing of nitrogen at a flow rate of 300 mL / min, and was kept for 2 hours. After naturally cooling to room temperature under the protection of nitrogen, the manganese-iron bimetallic oxide loaded granular activated carbon was obtained.

[0073] Application Example 1: The manganese-iron bimetallic oxide loaded granular activated carbon prepared in Example 1 was ground into powder (more than 80 mesh), and 3 portions of 35 mL of rhodamine B solution with a concentration of 10 mg / L were prepared. 0.0075 g of the composite material powder and 0.015 g of PMS were added into one portion of the solution, and 0.0075 g of the composite material powder or 0.015 g of PMS was added into the other two portions of the solution respectively. After shaking in a shaking table at a speed of 200 revolutions per minute for 10 minutes, the supernatant was filtered through a 0.22 μm disposable needle filter, and the absorbance of the solution at 554 nm was measured by a UV-visible spectrophotometer. The concentration of the residual rhodamine B in the solution was calculated by combining the rhodamine B absorbance-concentration standard curve, and the rhodamine B removal rate of the three experimental batches was determined.

[0074] In the comparative experiments, the composite material powder prepared in Example 1 was replaced by the material powder prepared in Comparative Example 1 and Comparative Example 2, and the other operation conditions were unchanged.

[0075] The experimental results are shown in Table 1. Figure 5 The three preparation schemes obtained the catalytic materials which had adsorption performance by themselves, and the removal rates of rhodamine B in the solution reached 34.59% (Example 1), 12.37% (Comparative Example 1) and 32.77% (Comparative Example 2) respectively, while the oxidation ability of PMS alone was weak, and the removal rate of rhodamine B was only 3.60%.

[0076] The three kinds of catalytic materials were used in combination with PMS, and the removal rates of 68.70% (Example 1), 55.87% (Comparative Example 1) and 50.96% (Comparative Example 2) were achieved in the same time, which indicated that the combination of the catalytic materials and PMS triggered a synergistic catalytic effect. The catalytic performance of the sample of Example 1 was obviously better than that of the sample of Comparative Example 1 with the same mass, which indicated that the dispersion effect of the carrier was beneficial to the improvement of the catalytic performance. The catalytic degradation rate of rhodamine B of the sample of Comparative Example 2 was low, which indicated that manganese chloride and iron chloride were more suitable as the precursors of metal oxides than manganese acetate tetrahydrate and iron nitrate nonahydrate.

[0077] After the experiment of three kinds of catalytic materials catalyzing PMS to degrade rhodamine B, the reaction solution was extracted by a syringe, filtered by a 0.22 μm needle filter, and then the concentrations of manganese and iron in the reaction solution were determined by inductively coupled plasma optical emission spectrometer (ICP-OES).

[0078] The manganese elution concentrations were 0.085 mg / L (Example 1), 1.392 mg / L (Comparative Example 1) and 1.988 mg / L (Comparative Example 2), respectively, and the iron elution concentrations were all not detected. The above results show that the thermal decomposition characteristics of manganese acetate tetrahydrate and iron nitrate nonahydrate and the limitation of the activated carbon carrier itself can significantly improve the stability of the catalytic material.

[0079] Application Example 2: The catalytic degradation performance of the granular activated carbon loaded with manganese-iron bimetallic oxide prepared in Example 1 on lomefloxacin in water was investigated by continuous flow catalytic experiment, and the practical application potential was evaluated. The schematic diagram of the experimental device is shown in Figure 6 The fixed bed reactor has an inner diameter of 1 cm, and the activated carbon is loaded to a height of 5.5 cm. The concentrations of lomefloxacin solution and PMS solution are both 1 mg / L, and the flow rates are 0.25 mL / min and 0.4 mL / min, respectively.

[0080] The effluent at different time points was collected by an automatic partial collector, and the absorbance of the solution at 285 nm was determined by a UV-visible spectrophotometer. Combined with the absorbance-concentration standard curve of lomefloxacin, the concentration of residual lomefloxacin in the solution and the corresponding removal rate were calculated.

[0081] The lomefloxacin removal rates at different time points are shown in Figure 7 During the nearly 17 hours of running time, the degradation rate of lomefloxacin remained above 90%, indicating that the catalytic material can be applied to the fixed bed continuous flow advanced oxidation water treatment scene.

[0082] The above only describes the preferred embodiments of the present application and is not used to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a granular activated carbon material loaded with manganese-iron bimetallic oxide, characterized in that, Includes the following steps: S1. Determine the saturated water absorption volume of granular activated carbon per unit mass; S2. Dissolve manganese acetate tetrahydrate and ferric nitrate nonahydrate completely in deionized water, then add citric acid monohydrate, and stir the reaction thoroughly to obtain a manganese-iron-citric acid sol system. S3. Place the dried granular activated carbon in a manganese-iron-citric acid sol system, stir evenly, and let stand to obtain iron-manganese impregnated granular activated carbon. S4. Transfer the iron-manganese impregnated granular activated carbon to an oven for drying to obtain dried iron-manganese impregnated granular activated carbon; S5. The dried iron-manganese impregnated granular activated carbon is calcined under oxygen-limited or oxygen-free conditions to obtain granular activated carbon material loaded with iron-manganese bimetallic oxides.

2. The method for preparing particulate activated carbon material supported on manganese-iron bimetallic oxide according to claim 1, characterized in that, The raw materials for the granular activated carbon include one or more of coal-based activated carbon, fruit shell activated carbon, and secondary-formed columnar carbon derived from the above raw materials; the particle size range of the granular activated carbon is 0.2-5 mm. The method for determining the saturated water absorption volume of the granular activated carbon includes: Completely immerse completely dried granular activated carbon in deionized water and let it stand for 24 hours. Then, use a filter made of non-absorbent material to perform solid-liquid separation. After no more liquid drips, weigh the saturated activated carbon and determine the saturated water absorption volume per unit mass of activated carbon using the following formula: , Among them, V 饱和 The saturated water absorption volume per unit mass of activated carbon, in ml / g; m 湿 The mass of water-saturated activated carbon is expressed in g; m 干 The mass of completely dried granular activated carbon is given in grams; ρ is the density of water, expressed in g / cm³. 3 .

3. The method for preparing granular activated carbon material supported on manganese-iron bimetallic oxide according to claim 1, characterized in that, The molar ratio of manganese acetate tetrahydrate to ferric nitrate nonahydrate is 1:(2-3.5); the molar ratio of citric acid monohydrate to the total amount of manganese acetate tetrahydrate and ferric nitrate nonahydrate is (1.2-1.5):1; The manganese-iron-citric acid sol system is obtained by stirring and reacting at room temperature for 30-120 minutes.

4. The method for preparing granular activated carbon material supported on manganese-iron bimetallic oxide according to claim 3, characterized in that, Rare earth metal salts are added during the process of completely dissolving manganese acetate tetrahydrate and ferric nitrate nonahydrate in deionized water. The molar ratio of the rare earth metal salts to the total amount of manganese acetate tetrahydrate and ferric nitrate nonahydrate is (0.05-0.1):

1. The rare earth metal salts include cerium nitrate hexahydrate and / or lanthanum nitrate hexahydrate.

5. The method for preparing particulate activated carbon material supported on manganese-iron bimetallic oxide according to claim 1, characterized in that, The amount of dried granular activated carbon added in step S3 is calculated using the following formula: m=V 水 / V 饱和 , Where m is the mass of dried activated carbon added, in g; V 水 V represents the volume of deionized water in step S2, in ml; 饱和 The saturated water absorption volume per unit mass of activated carbon, in ml / g; The settling time in step S3 is 6-24 hours.

6. The method for preparing particulate activated carbon material supported on manganese-iron bimetallic oxide according to claim 1, characterized in that, The drying temperature in the oven in step S4 is 80-120℃, and the drying time is 6-24h. During the drying process in the oven, the material is turned over every 5 minutes within the first 30 minutes of drying.

7. The method for preparing particulate activated carbon material supported on manganese-iron bimetallic oxide according to claim 1, characterized in that, The calcination process in step S5 includes the following steps: Dry iron-manganese impregnated granular activated carbon is placed in a crucible, covered and wrapped with double-layer aluminum foil, and then placed in a muffle furnace for calcination. The heating rate of the muffle furnace is 1-10℃ / min, the maximum calcination temperature is 400-700℃, and the holding time is 1-6h. Alternatively, dried iron-manganese impregnated granular activated carbon can be placed in a crucible and then transferred to an atmosphere tube furnace for calcination under inert gas protection. The heating rate in the atmosphere tube furnace is 1-10℃ / min, the maximum calcination temperature is 400-700℃, and the holding time is 1-6h. The inert gas includes high-purity nitrogen and / or argon, and the gas flow rate is 50-300mL / min.

8. The method for preparing particulate activated carbon material supported on manganese-iron bimetallic oxide according to claim 7, characterized in that, The calcined granular activated carbon loaded with manganese-iron bimetallic oxide was soaked in a 0.1-0.5 mol / L tetrabutyl titanate-ethanol solution and stirred at room temperature for 1-2 hours. The activated carbon is transferred to an oven and dried at 80-120℃ for 6-24 hours, and then calcined in air at 400-500℃ for 1-2 hours to generate anatase TiO2 in situ on the surface of the activated carbon.

9. A granular activated carbon material loaded with manganese-iron bimetallic oxide, characterized in that, The granular activated carbon material loaded with manganese-iron bimetallic oxide is prepared by the method for preparing granular activated carbon material loaded with manganese-iron bimetallic oxide according to any one of claims 1-8.

10. The application of a granular activated carbon material supported on manganese-iron bimetallic oxide, characterized in that, The granular activated carbon material prepared by the method of preparing granular activated carbon material loaded with manganese iron bimetallic oxide according to any one of claims 1-8 is applied in the fields of environmental functional materials and water treatment technology.

Citation Information

Patent Citations

  • Supported Fe-Mn carbon fiber catalyst for catalyzing low-concentration VOCs (Volatile Organic Compounds) as well as preparation method and application thereof

    CN119346129A

  • Modified iron-manganese bimetallic material and preparation method and application thereof

    CN112403445A

  • Manganese ferrite / biochar composite material as well as preparation method and application thereof

    CN114768819A

  • Preparation method of magnetic biochar with catalysis and specific phosphorus adsorption performance

    CN115318300A

  • Preparation method and application of biological source iron and manganese oxide catalyst

    CN116440922A